2017
DOI: 10.1609/aaai.v31i1.10611
|View full text |Cite
|
Sign up to set email alerts
|

Proportional Justified Representation

Abstract: The goal of multi-winner elections is to choose a fixed-size committee based on voters’ preferences. An important concern in this setting is representation: large groups of voters with cohesive preferences should be adequately represented by the election winners. Recently, Aziz et al. proposed two axioms that aim to capture this idea: justified representation (JR) and its strengthening extended justified representation (EJR). In this paper, we extend the work of Aziz et al. in several directions. First, we ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 18 publications
2
67
0
Order By: Relevance
“…We show that the sequential variant satisfies PJR, making it the first known polynomial-time computable method with this property. 1 Moreover, we show that the optimization variants satisfy perfect representation (PR), a further representation axiom introduced by Sánchez-Fernández et al (2017). The latter result provides a contrast to PAV, which is known to violate PR.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…We show that the sequential variant satisfies PJR, making it the first known polynomial-time computable method with this property. 1 Moreover, we show that the optimization variants satisfy perfect representation (PR), a further representation axiom introduced by Sánchez-Fernández et al (2017). The latter result provides a contrast to PAV, which is known to violate PR.…”
Section: Introductionmentioning
confidence: 85%
“…In the setting of approval-based committee voting (Kilgour 2010), Aziz et al (2015a) proposed two representation axioms: justified representation (JR) and its strengthening extended justified representation (EJR). Later, Sánchez-Fernández et al (2017) observed that EJR is not compatible with what they call perfect representation (PR) and proposed an axiomatic property, proportional justified representation (PJR), that is. EJR implies PJR, which in turn implies JR. Aziz et al (2015a) and Sánchez-Fernández et al (2017) showed that most common committee voting rules fail EJR and PJR.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations